Analisis Mekanisme Pengelolaan Dana Kapitasi Pada Klinik Pratama di Kecamatan Pedurungan Kota Semarang - Listia Ayuni Nur Afifah; Septo Pawelas Arso; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Pratama Clinic is a health care facility that organizes individual health that provides basic medical health services. Pratama Clinic is a private Primary Health Care/not owned by the Government so it is not under the Department of Health. Pedurungan District is one of the districts with the highest population in Semarang City and has the highest number of pratama clinics. Capitation fund management is a procedure for budgeting, implementation, administration (utilization), and accountability of capitation fund. BPJS Kesehatan must pay capitation and non-capitation tariffs to perform basic health services provided by pratama clinics to participants in the National Health Insurance (JKN) program. This study aims to describe the mechanism of managing capitation funds at the Pratama clinic in Pedurungan District, Semarang City. This study is a qualitative study with in-depth interviews and observations with Owners, Admins, and Doctors at the Pratama Clinic.The results show that all Pratama clinics do not make plans for capitalization and expenditure. BPJS Kesehatan is always on time to pay capitation funds, which is every 15th. Not all pratama clinics determine the amount of capitation fund allocation for health services and support for operational costs of health. Pratama Clinic also does not carry out accountability of capitation funds, but only makes reports requested by BPJS Kesehatan or other agencies. To overcome this, the role of leadership is needed in managing capitation funds at the Pratama Clinic optimally and BPJS Kesehatan needs to make regulations related to the management of capitation fund at Pratama clinic.